Contemplative thinking among students of middle school (Journal of the College of Education for Women, 2019)
That the strength of the community and its cohesion and integrity of its structure and morals and the prevailing relations and the strength of its institutions depends all on the numbers of a generation of students saturation of the culture of the nation and proud of its heritage and maintained their customs and traditions and voluntarily accept its laws. Students are the future leaders who are more than capable of giving, they represent class they are educated conscious backbone of the nation and the subject of their hopes, and their wealth and energies warehouse actors produced, and one of the key pillars in achieving developments in all areas of life.Based on the above, the current research aims to identify:. reflective thinking when middle school students.12.differences with statistical significance in thinking contemplative depending on variables (sex, section).Identify current research students of fifth grade preparatory of both sexes, and branches (scientific and literary) in high school and middle school affiliated to the Second Karkh Directorate of the province of Baghdad, for the academic year (2015-2016).In order to achieve objectives of the research, the researcher build reflective thinking which consisted of (29) items as the final measure, the researcher has unearthed the psychometric properties of the scale of validity and reliability.The sample consisted of current research (410) students of (205) male to specialize Alalumbly and literary and (205) females scientific and literary specialty selected stratified random way, and after processing the data statistically researcher found the following results:1.The fifth preparatory grade students are characterized by possessing a meditative reflection.2.Do not Tugod statistically significant differences depending on variables (sex, section) and bilateral interaction between the two variables.In light of these results the researcher set a number of recommendations and suggestions, including:1.Care developed a Human Studies studied by students to activate reflective thinking they have a curriculum.2.on based on the educational process by providing an appropriate environment for the development of descriptive reflective thinking of the students.use of teaching aids by the teachers and make practical experiences in the classroom and away from traditional styles.The researcher set a number of proposals in prospective studies, including:-a study on samples from the other students to study stages.12.a longitudinal study (developmental) for the growth and development of reflective thinking among primary school students